Economic burden of patients with leading cancers in China: a cost-of-illness study - Wu, Ziting; Yu, Yiwen; Xie, Feng; Chen, Qiushi; Cao, Zhong; Chen, Simiao; Liu, Gordon G. (BMC health services research, 2024)
China accounts for 24% of newly diagnosed cancer cases and 30% of cancer-related deaths worldwide. Comprehensive analyses of the economic burden on patients across different cancer treatment phases, based on empirical data, are lacking. This study aims to estimate the financial burden borne by patients and analyze the cost compositions of the leading cancers with the highest number of new cases in China.